Síntese, caracterização e reatividade do complexo trans-Ru(NH3)4(BPA)(NO)](PF6)3 , sendo BPA = (1,2-bis(4-piridil)etano. - Silveira, Francisco Fernando (2018)
Blood pressure is regulated by several factors, such as vasoconstriction and peripheral resistance, and when conditions prevail that contract the arteries, has been the hypertension, in which values above 140/90mmHg. When analyzing the increasing number of deaths due to cardiovascular diseases it should be remembered that hypertension is associated with aging, eating habits and sedentary lifestyle. Nitric Oxide (NO), molecule produced endogenously from the conversion of L-arginine in L-citrulline, is the main regulator of blood pressure. Stable ruthenium nitrosyl complexes have been searched in order to release NO thus acting on vascular smooth muscle relaxation. In view of the foregoing, this paper aims to synthesize, characterize and perform reactivity studies of a new compound, the trans-[Ru(NH3)4(BPA)(NO)](PF6)3. The characterization of nitrosilocomplex was performed by means of spectroscopic techniques (Infrared region vibrational spectroscopy, electron spectroscopy in the ultraviolet and visible regions), 1H-nuclear magnetic resonance, and cyclic voltammetry. The synthesized complex was then studied as to its ability to release NO° and the application of electric potential suggests the formation of aquo-complex. The reduction by GSH indicates that there is the possibility of NO° release occurring. The spectrophotometric titration showed that the conversion pH of the NO+/NO2- species to the trans-[Ru(NH3)4(BPA)(NO)](PF6)3 complex is 11.59. In addition, reactivity of nitrosyl complex facing superoxide radical was studied. The results suggested that compound presented antioxidant activity against free radical. The results indicate the obtaining of a new compound with the potential to act as a NO-releasing agent in the body. Cytotoxicity studies, as well as vasodilation assay should be performed to assess its efficacy as a vasodilator potential.